STRATEGY TO IMPROVE THE QUALITY OF PERFORMANCE OF MAINTENANCE SECTION EMPLOYEES AT PT. ADICIPTA BOGA INTIPRIMA TANGERANG - Raharjo, Teguh; Ramadhan, Muhammad Zaid; Mardiana, Nana; Suherna, Endang; Moeljadi, Moeljadi (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This research focuses on strategies for improving the quality of performance of maintenance employees at PT. Adicipta Boga Intiprima. The maintenance department has an important role in maintaining the company's smooth operations, however the performance of employees in this section has decreased in recent years. Problems such as lack of motivation, limited technical skills, and ineffective communication between management and employees were identified as factors causing the decline in performance. This research uses a qualitative approach with a case study method to understand in depth the factors that influence the performance of maintenance employees as well as strategies that can be implemented to improve the quality of performance. Data was collected through in-depth interviews, participatory observation and documentation, with research subjects consisting of maintenance employees and managers at PT. Adicipta Boga Intiprima. The results of this research indicate that factors such as effective leadership, supportive organizational culture, and continuous training are important elements in improving employee performance. Apart from that, a performance-based incentive system and improved internal communication between management and employees also play a significant role in motivating employees to work better. Based on these findings, several performance improvement strategies were prepared that could be implemented at PT. Adicipta Boga Intiprima to achieve more optimal performance and operational efficiency.